التوجّهات الحديثة لسلطات القاضي الإداري في مجال تنفيذ الأحكام الصّادرة ضدّ الإدارة - غنادرة, عائشة (جامعة الوادي University of Eloued, 2016)
لطالما ساد الاعتقاد أن دور القاضي الإداري ينتهي بمجرد التصريح بالحكم الفاصل في النزاع المعروض عليه، كما ساد الاعتقاد أن تنفيذ الأحكام القضائيّة موكول لجهة الإدارة دون سواها. غير أنّ انتشار مفهوم دولة القانون، وتكريس مبدأ استقلال القضاء نتج عنه، اعتبار أنّ مهمة القاضي الإداري لا تنتهي بمجرد التصريح بالحكم الفاصل في موضوع الدعوى، بل أدّى إلى إلزام الإدارة على تنفيذ أحكام القضاء باعتبارها شخص من أشخاص القانون العام، حيث أنّه ما الفائدة من الاعتراف للأفراد بالحقّ في اللّجوء للقضاء ورفع دعاوى ضدّ الإدارة، وعليه عندما يحسم القاضي الإداري في النزاع تبادر جهة الإدارة بالامتناع عن تنفيذ الحكم القضائي الصّادر ضدّها. لهذا وضمانا لتنفيذ الحكم القضائي الصّادر في الدعاوى الإدارية منحت للقاضي الإداري مجموعة من السّلطات التي يستطيع بها حمل الإدارة على الرّضوخ لحكمه وتنفيذه إياه، تمثّلت هاته السّلطات في البداية في تدخّل القاضي الإداري عن طريق دعويين قضائيتين (دعوى الإلغاء والمسؤولية الإدارية لمخالفة حجيّة الأحكام القضائية الصّادرة ضد الإدارة) وهو ما أطلق علية الفقه تسمية السّلطات التقليدية، لكن مع عدم فعاليّة هاته السّلطات بمرور الوقت تدخّل المشرّع لمنح سلطات أخرى تعالج هذا التعنّت بعدم التنفيذ تمثلت في سلطتي الأوامر التنفيذية وسلطة الغرامة التهديدية وهو ما أطلق عليه الفقه تسمية السّلطات الحديثة. Abstract: For as long as it was believed that the role of the administrative judge ends once the permit governing the separation in the dispute before it, as it was believed that the implementation of judicial decisions is entrusted to the administrative body only. However, the spread of the concept of the rule of law, and reinforcing the principle of independence of the judiciary resulting from it, considering that the administrative judge job does not end once the permit governing the separation in the merits of the case, it led to compel the Department to implement the provisions of the judiciary as one of the persons of public law, as it is the interest of recognition to individuals the right to asylum and to eliminate lawsuits against the administration, and when the administrative judge settle the dispute, initiated the administrative body to refrain from the implementation of the court ruling issued against them. For this and to ensure implementation of the court ruling issued in the administrative proceedings administrative judge awarded a group of authorities that can carry out administration to bow to his rule and executed him. It represented these circumstances the authorities initially enter the administrative judge by the two proceedings (procedure annulment and administrative responsibility for violating the authoritative judicial judgments against the administration) Désignation de la jurisprudence surnommé autorités traditionnelles, But with the ineffectiveness of these circumstances the authorities over time entering the legislature to grant other authorities dealing with this intransigence, the non-implementation was the branches of executive orders and threatening the authority of the fine, which the so-called modern jurisprudence nominate authorities.
Keywords: سلطات القاضي الإداري؛ تنفيذ الأحكام؛ الأحكام القضائيّة؛ إلزام الإدارة؛ إستقلال القضاء؛ الدعاوى الإداريّة؛ القانون العام